Laser additive manufacturing and post-heat treatment on microstructure and mechanical properties of 9Cr steel. (August 2022) - Feng, Junyi; Zhang, Peilei; Jia, Zhiyuan; Yu, Zhishui; Fang, Chao; Yan, Hua; Shi, Haichuan; Tian, Yingtao; Xie, Fan
Abstract: 9Cr steel is a material that has been widely used in pressure vessel parts in thermal power plants and nuclear power plants, and has good high-temperature creep properties. Laser Melting Deposition (LMD) is a promising method for preparing complex 9Cr steel components. It provides a rare opportunity to improve existing designs and produce fine features and complex geometries with higher efficiency. The LMD-9Cr steel sample has high density, the maximum tensile strength of the sample is 1057.75 MPa, which is much higher than the standard cast 9Cr steel of 650 MPa. We use 760 °C tempering heat treatment, after heat treatment, the average grain size of the material is reduced, the Charpy impact performance is improved, and the tensile strength and microhardness are slightly reduced. Although the tempering heat treatment greatly reduces the average grain size of the sample by 35.59%, but at the same time the tempering heat treatment greatly reduces the high dislocation density of lath martensite, and the supersaturation behavior of Cr, W and C elements weakens the effect of solid solution strengthening. In addition, through the nanoindentation test, we found that although the M23 C6 precipitated phase can harden the material, at the micro level, the elastic modulus and nano-hardness of the precipitated phase are lower than that of the homogeneous phase. Highlights: 9Cr steel was fabricated by laser coaxial powder feeding additive. C The constructed LMD-9Cr sample has high density, the maximum tensile strength of the sample is 1057.75Mpa, which is much higher than the standard cast 9Cr steel of 650 MPa. Tempering heat treatment greatly reduces the high dislocation density of lath martensite Effect of crystallization on mechanical properties.